Fotoreduksi Logam Krom (VI) Menggunakan Fotokatalis Lapis Tipis TiO2-Mn Mesopori dengan Bantuan Lampu Tungsten - Kapti Riyani; Tien Setyaningtyas; Agus Soleh (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2016)
Hexavalent chromium is a heavy metal that is toxic and give bad impact to human living. Maximum consentration of hexavalent chromium of solution that can be accepted is 0,05 ppm. This research was conducted to reduce hexavalent chromium by photoreduction method using mesophorous TiO2-Mn thin film photocatalyst with a tungsten lamp. Tha aim of this research is to obtain optimum ratio of TiO2-Mn (100:0; 99:1; 98:2; 97:3; and 96:4) to reduce hexavalent chromium. A thin film was synthesized by photodeposition method with calcination temperature 4000C for 6 hours. TiO2-Mn was crushed and made into coloidal phase with PEG 1000, then coated on a glass plat (9X4 cm). Thin film was tested to reduce hexavalent chromium with tungsten lamp and its concentration was measured by UV-Visible Spectrophotometer at wave length of 541 nm. The result showed that 99:1 is an optimum ratio of TiO2-Mn and it reduce hexavalent chromium up to 52,3 %. The decrease of hexavalent chromium concentration caused by the photoreduction process in mesophorous TiO2-Mn